1979
DOI: 10.1111/j.1365-2672.1979.tb00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐resistant Bacteria in Pasteurized Whole Egg

Abstract: Samples of egg melange taken from an egg packing station contained an average of 7·3 x 104 organisms/ml which survived laboratory pasteurization at 65°C for 3 min. Many of the organisms surviving pasteurization were found to be coryneform bacteria related to Microbacterium lacticum which could be differentiated into several groups. The remainder were a miscellaneous collection of unidentified cocci and coccobacilli and some Bacillus spp. The coryneform bacteria were shown to be the most heat‐resistant isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…The observed decline in viability that precedes growth on transfer to whole egg of cells of Strep, faecium grown in heart infusion broth is not peculiar to this organism and a similar result has been reported with Microbacterium lacticum NGDO 747 (Payne et al, 1979). The alternative explanation, that the increase in viable count was due to the growth of a low level of contaminants, is unlikely because the cultures appeared identical to the inoculum.…”
Section: Effect Of Temperature On Survival In Raw and Pasteurised Eggsupporting
confidence: 69%
See 2 more Smart Citations
“…The observed decline in viability that precedes growth on transfer to whole egg of cells of Strep, faecium grown in heart infusion broth is not peculiar to this organism and a similar result has been reported with Microbacterium lacticum NGDO 747 (Payne et al, 1979). The alternative explanation, that the increase in viable count was due to the growth of a low level of contaminants, is unlikely because the cultures appeared identical to the inoculum.…”
Section: Effect Of Temperature On Survival In Raw and Pasteurised Eggsupporting
confidence: 69%
“…Barnes et al, 1978Barnes et al, 1978 Preparation of sterile egg Liquid whole egg and egg albumen were prepared as previously described (Corry and Barnes, 1968;Payne et al, 1979). Eggs were stored for 3 d at 1 °C prior to breaking out the contents.…”
Section: Maintenance Of Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram negative bacteria were predominant in the unpasteurized whites. Seviour and Board (1972), , and Suzuki et al (1979) reported that Gram negative bacteria such as Aeromonas, Enterobacteriaceae, Flavobacterium, and Pseudomonas were predominant in unpasteurized liquid egg products and in spoiled shell eggs, and Shafi et al (1970), Payne et al (1979), and Payne and Gooch (1980) stated that gram positive bacteria such as Bacillus, coryneform, Micrococcus, and Staphylococcus were predominant in pasteurized liquid egg products. The microbiological findings obtained in this study agreed generally with the results obtained by these researchers.…”
Section: Resultsmentioning
confidence: 96%
“…at 6O"C)to assure a 9 log cycle (9D) reduction in the number of Salmonella (USDA 1969). Heat resistant spoilage microorganisms, however, survive pasteurization and spoil the product if it is not held frozen (York and Dawson 1973;Shafi et al 1970 andPyne et al 1979). Increased thermal treatment followed by aseptic packaging h a s been suggested to produce a long shelf-life pasteurized LWE (PLWE) (Essary et al 1983;Hamid-Samimi et al 1984).…”
Section: Introductionmentioning
confidence: 99%